2017
DOI: 10.1016/j.ymthe.2017.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Intraceptor Nanoparticle for Neovascular Macular Degeneration: Preclinical Dose Optimization and Toxicology Assessment

Abstract: Neovascular age-related macular degeneration (AMD) is treated with anti-VEGF intravitreal injections, which can cause geographic atrophy, infection, and retinal fibrosis. To minimize these toxicities, we developed a nanoparticle delivery system for recombinant Flt23k intraceptor plasmid (RGD.Flt23k.NP) to suppress VEGF intracellularly within choroidal neovascular (CNV) lesions in a laser-induced CNV mouse model through intravenous administration. In the current study, we examined the efficacy and safety of RGD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 34 publications
0
8
0
2
Order By: Relevance
“…Integrins are essential in VEGF signaling in ocular NV. Although a few previous studies reported that RGD conjugation could actively target CNV, applying synthetic nanoparticles to conjugate with RGD or systemic administration of these particles diminished their clinical utility [ 33 , 34 , 35 , 36 ]. Here, we demonstrated that multiretinal cell-derived exosomes modified with an ASL system actively targeted CNV in a laser-induced CNV mouse model by promoting their uptake to overexpressed integrin v at the site of CNV.…”
Section: Discussionmentioning
confidence: 99%
“…Integrins are essential in VEGF signaling in ocular NV. Although a few previous studies reported that RGD conjugation could actively target CNV, applying synthetic nanoparticles to conjugate with RGD or systemic administration of these particles diminished their clinical utility [ 33 , 34 , 35 , 36 ]. Here, we demonstrated that multiretinal cell-derived exosomes modified with an ASL system actively targeted CNV in a laser-induced CNV mouse model by promoting their uptake to overexpressed integrin v at the site of CNV.…”
Section: Discussionmentioning
confidence: 99%
“…Саме тому було припущено, що anti-VEGF терапія значно покращить зір і якість життя пацієнтів із "вологою" фор-мою ВМД. Однак, приблизно одна третина пацієнтів не отримує ефекту від даної терапії через макулярний фіброз або атрофію тощо [13,17,18].…”
Section: вступunclassified
“…Targeted intraceptor nanoparticle therapy is administered intravenously and can cross the blood-retinal barrier, which is generally a major obstacle for intravenous delivery. Furthermore, this therapy is nontoxic in vivo, suggesting that this could provide a means for alternative drug delivery route to treat nAMD [60,61].…”
Section: New Therapies For Namd—thinking Beyond Anti-vegfsmentioning
confidence: 99%